Pengaruh Disiplin Kerja, Jasa Pelayanan, Motivasi Kerja Terhadap Kinerja Pegawai Di Puskesmas Bulu - Totok Sundoro (Jurnal Manajerial, 2022)
Background – The discovery of work discipline problems with employees not complying with the rules of working hours which have an impact on delays in completing work, services that employees feel are still not enough, and the tendency of employees who are only able to do their jobs without caring about other tasks. Aim - To determine the effect of work discipline, service, work motivation on employee performance at Bulu Health Center. Design / Methodology / Approach – This research is a quantitative research. The research sample was all employees of Bulu Health Center as many as 35 respondents. The sampling technique used was total sampling. Analysis of research data using multiple linear regression analysis with the help of the IBM SPSS Statistics 23 program as statistical data processing. The hypothesis is that it is suspected that there is work discipline, work services, work motivation and employee performance at Bulu Health Center. Result and Discussion - The results of this study obtained the value of the Model Summary table, the R value of 0.806, which means that it shows a strong relationship. R square is the coefficient of determination that shows the percentage of the influence of variables X1, X2, and X3 on Y. The value of R square of 0.706 indicates that the effect of work discipline, service, work motivation together (simultaneously) on employee performance is 70.6 %, while the remaining 29.4% is influenced by other factors. The regression equation formed Y = 1.031 + 0.245X1 + 0.225X2 + 0.284X3 a positive sign means that if work discipline (X1), Services (X2) and work motivation are increased, it can increase the Performance of Service Employees at Bulu Health Center (Y). Work discipline has a positive effect on employee performance with a value of p = 0.037 (p <0.05); Services have a positive effect on employee performance with a value of 0.035 (p<0.05) and motivation has a positive effect on employee performance with a value of p=0.034 (p<0.05). Conclusion - Based on the research results, it is proven that all hypotheses can be accepted (Work Discipline, Services and Work Motivation have a significant effect on Employee Performance). Research Implications - It is hoped that the results of this study can add insight and literature related to improving employee performance by paying attention to aspects of work discipline, service and work motivation. Research Limitations - The instrument used is only a questionnaire, so the data only comes from filling out the questionnaire where the respondent has a perception depending on the understanding of the questions listed in the questionnaire, so that there may be differences in respondents' perceptions and the possibility of linear bias, namely the respondent's answer that is not in accordance with their own reality.